Interdependence between Islamic capital market and money market in Malaysia / Che’ Khalilah Mahmood - Mahmood, Che’ Khalilah (2014)
This study investigates VAR Toda-Yamamoto’s causality test between Islamic capital market (FBMESI) and money market (I1MMR) with macroeconomic variables (BLR, M2, ER, IPI, GDP, CPI, WOP, GDPC, VIX, and FRR). The purpose of this study is to analyze the information content of Islamic capital market and Islamic money market with respect to several macroeconomic indicators. The Toda-Yamamoto bivariate and multivariate causality test was employed. The findings from the bivariate and multivariate causality test show that the IIMMR either a one-way or two-way causality relationship with all macroeconomic variables employed (BLR, M2, ER, IPI, GDP, CPI, WOP, GDPC, VIX, and FRR). FBMESI have only one-way or two-way causal relationship with (BLR, M2, IPI, GDP, CPI, WOP, GDPC, and FRR). ER, IPI, and FRR and a two-way causal relationship with GDPM in a bivariate and multivariate causality test. It can be conclude that from the Toda-Yamamoto’s bivariate and multivariate causality test, IIMMR have more information content related to macroeconomic variables compared to FBMESI, thus more suitable to be the indicator for monetary policies for regulator (BNM)